设A为n阶可逆矩阵,则(-A)的伴随矩阵(-A)*等于____。
A: -A*
B: .A*
C: (-)nA*
D: (-)n-1A*
A: -A*
B: .A*
C: (-)nA*
D: (-)n-1A*
D
举一反三
- 设A为n阶可逆矩阵,则(-A)的伴随矩阵(-A)*等于____。 A: -A* B: .A* C: (-)nA* D: (-)n-1A*
- 设A为n阶可逆矩阵,则(-A)*等于 A: -A* B: A* C: (-1)nA* D: (-1)n-1A*
- 设A为n阶可逆矩阵,则(-A)的伴随矩阵(-A)*等于()。 A: -A* B: A* C: (-1)A* D: (-1)A*
- 设A为n阶可逆矩阵,则(-A)的伴随矩阵(-A)*等于()。
- (1996年)设n阶矩阵A非奇异(n≥2),A*是矩阵A的伴随矩阵,则(A*)*等于 A: |A|n-1A B: |A|n+1A C: |A|n-2A D: |A|n+2A
内容
- 0
设n阶矩阵A非奇异(n≥2),A*是矩阵A的伴随矩阵,则()。 A: (A*)*=|A|n-1A B: (A*)*=|A|n+1A C: (A*)*=|A|n-2A D: (A*)*=|A|n+2A
- 1
设A为n阶可逆矩阵,A*是A的伴随矩阵,则 。 A: |AD|=|A| B: |A*|=|A|n-1 C: |A*|=|A|n D: |A*|=|A-1
- 2
设 A 为 n 阶可逆矩阵 , 则 ( - A ) * 等于
- 3
设A为n阶可逆矩阵,则(-A)的伴随矩阵(-A)*等于( )。 A: -A<SUP>*</SUP> B: A<SUP>*</SUP> C: (-1)<SUP>n</SUP>A<SUP>*</SUP> D: (-1)<SUP>n-1</SUP>A<SUP>*</SUP>
- 4
设A为n阶可逆矩阵,A*是A的伴随矩阵,则 A: (A*)*=|A|n-1A. B: B. C: C. D: D.